International Workshop on Assessing Models of Public-Private Partnership for Irrigation Development: intro and objectives - International Food Policy Research Institute (2018)
AMPPPIDA International Workshop on Assessing Models of Public-Private Partnership for Irrigation Development Mar 13, 2018 - 08:30 am to 02:00 pm GMT